Pattern of Hemorrhagic Disorders in Patient with Bleeding Manifestations - Quadir, SM Mahbubul; Waheed, Md Imran; Yasmin, Sabina (IAHS Medical Journal, 2022)
Background: Adults with undiagnosed bleeding disorders present in a variety of ways. While severe bleeding disorders and most congenital bleeding disorders initially present during childhood, conditions associated with heavy bleeding only after a haemostatic challenge (Such as surgery or trauma) often present during adulthood. The evaluation of a patient with a possible bleeding disorder can be one of the most challenging referrals in hematology practice. In the absence of much evidence-based outcomes data, the practitioner’s experimental judgment will be called upon to formulate a working diagnosis and management plan in many instances. The present study is aimed to find out the incidence of diseases presenting with bleeding manifestations and their clinical patterns with age and sex relationship. It is also important to establish the pathological correlation with clinical features. Materials and methods: This observational study was carried out in the Department of Hematology, Armed Forces Institute of Pathology, Dhaka cantonment for a period of one year between 01 January 2018 to 31 December 2018. A total of 57 cases of all ages with bleeding manifestations were studied clinically and appropriate laboratory investigations were carried out to find the causes of bleeding. Statistical analysis was done by using SPSS for windows version 17. c2 test was used as the tests of significance and p value <0.001 was accepted as the level of significance. Results: Out of 57 cases, 21(36.84%) patients were found to have acute leukemia, 15(26.32%) patients were idiopathic thrombocytopenic purpura, 11(19.30%) patients had haemophilia and 10(17.54%) patients were diagnosed as hypoplastic anemia. Among the bleeding manifestations, purpura was found in 42(73.68%) patients, gum bleeding in 24(42.11%) patients, melaena in 13(22.81%) patients, epistaxis in 11(19.30%) patients, menorrhagia in 09(15.79%) and bleeding inside joint cavity in 08(14.04%) patients. In this series, 11 cases of haemophilia, a sex linked bleeding disorders were diagnosed where 05(45.45%) cases had no positive family history. Conclusion: The successful management of bleeding manifestation depends upon the ability to make a quick diagnosis, so that a rapid and adequate therapy can be adopted. IAHS Medical Journal Vol 5(1), June 2022; 74-77